ANALYSIS OF THE IMPACT OF CROSS-SECTIONAL MODIFICATION ON THE FLOOD POTENTIAL OF GUNTUNG PAYUNG RIVER USING HEC-RAS SOFTWARE - Pernanda, Yogie Setiawan; Nashrullah, Eddy (Universitas Lambung Mangkurat, 2025)
The Guntung Payung River in Banjarbaru City has undergone a structural cross-section modification from a box culvert to a bridge to address flooding caused by the inability of the existing cross-section to accommodate peak rainfall discharge. This study employed a Steady Flow 1D hydraulic simulation using HEC-RAS version 6.5 to analyze the impact of structural cross-section changes on water surface elevation and flood inundation area. The data used included river cross-section measurements, maximum daily rainfall over the past 20 years, and a Digital Elevation Model (DEM) map. The design discharge was calculated using the Rational Method for return periods of 2, 5, 10, 20, and 25 years. The results indicated that, for a 25-year return period, the water surface elevation at the downstream section (STA 0+190.75) decreased from 5.05 m to 3.75 m, and the inundation area was reduced by 61.15%. Conversely, the upstream section (STA 0+3116) showed no significant changes in water surface elevation or inundation area. These results indicate that the cross-section structure change is more effective in reducing flood potential downstream but does not impact the upstream area. Keywords: Guntung Payung River, HEC-RAS, Steady Flow 1D, cross-section structure change, water surface elevation, inundation area.